IBUPROFEN AND ITS DIFFERENT ANALYTICAL AND MANUFACTURING METHODS: A REVIEW - Bashyal, Sagar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Ibuprofen is a nonsteroidal anti-inflammatory drug, and many of its similar class includes aspirin, indomethacin (Indocin), naproxen (Aleve), nabumetone (Relafen), and many others. This drug is used in moderate pain, fever, and inflammation, which is promoted by the release in the body of chemicals called prostaglandins. According to the IUPAC, it is (RS)-2-(4-(2-methylpropyl)phenyl)propanoic acid. The original synthesis of ibuprofen by the Boots Group started with the compound 2-methylpropyl benzene. Ibuprofen blocks the enzyme that makes prostaglandins (cyclooxygenase), resulting in lower levels of prostaglandins that help in reducing inflammation, pain, and fever. This review is focused on various chemical and functional properties and experimental studies of ibuprofen including various detection methods such as potentiometric, ultraviolet spectrophotometric, gas chromatography, high-performance liquid chromatography (HPLC), and reverse-HPLC which can also be used for the extraction, quantification, and quality analysis.